Udq 631. 312:631.51 Choosing the Plowshares of Fertilizers and Base of Their Basic Parameters - Xudoyberdiev, T.S.; Boltaboev, B.R.; Tursunov, B.N.; Razzakov B.А. (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays the method of making furrows during the period of autumn plugging and flatting the lands of cotton plant in the fields is widely spread. In early spring the temperature of furrows is higher than flat fields. It gives the possibility to grind the clods of soil, to improve the soil granules and to make the furrows ready for sowing cotton seeds earlier. Fertilizing the lands at the same time with making furrows, result in increasing the cotton harvest. A number of researches were carried out in this field. These researches gave the opportunity to study the method of fertilizing the furrows in both lateral sides and the center of furrows in the form of a ribbon. However, the method of fertilizing the whole land in the period of making furrows was not studied enough. In order to solve this problem, we settled a plowshare in the fertilizer besides the streak so that to split the soil and open the way.We wanted to put fertilizers in 2 layers of the furrow i.e. into the basis and in 12…13 cm higher layer of the furrow by the help of fertilizer plowshares. The parameters i.e. the soil entering corner of the plowshare - and sharp corners - and were based. During the plowshare motion the corner of theplowshare that enters the soil was determined as 125о . It was determined with the help of weed remnants and soil clod cutting or slipping and passing from the plowshare. The limit of favorable sum composed the following: the minimal slip of soil granules or weeds from the plowshare is =155о...165о ; bent to the motion direction is 1=25о...35о. Also, we identified that sharp corner of the plowshare tip is =28о and the constructive sharpening corner is equal to =30о. Sharp corners of plowshare tips- and were identified by the help of considering the deformation and splashing and digging the soil and weeds by the plowshare along the width of the plowshare tip during its motion. , , , , , , , and